‘We kissed one another and parted good friends.’ On the expression of reciprocity in Early Modern English1 - Calle Martín, Javier (Onomázein, 2020)
Reciprocity in contemporary English is normally expressed by means of the compound pronouns each other and one another, both constructions used interchangeably and without any apparent difference in meaning, even though various factors have been proposed to account for the choice between the two alternatives. Among them, style stands out as the most convincing argument postulating the use of each other and one another in informal and formal contexts, respectively. In corpus-oriented grammars, their usage is explained in terms of register variation, each other being by far the most common form in all contexts while one another becomes relatively common in fiction and academic prose (Biber et al., 1999: 346-347). From a historical viewpoint, each other stems from those Old English constructions in which the quantifier ælc occurs with the alterity word o¯þer in neighbouring positions, while one another is a Late Middle English development of (the) one + (the) (an)other, where the first element is also the grammatical subject and the second the object (Haas, 2010: 63-68). Since then, both reciprocals have competed for more than five centuries for the expression of reciprocity in English and, interestingly enough, the dilemma is still unresolved, contradicting the general assumption that the competition between forms whose meaning is compatible is usually resolved either by the loss of one of them or by the adoption of a different (Kahlas-Tarkka, 2004: 132). The Early Modern English period becomes a crucial period in the history of reciprocals witnessing the transition from the discontinuous forms each the other and one the other to the fossilized constructions each other and one another. In the light of this, the present paper pursues the following objectives: a) to trace the origin, grammaticalization and univerbation of each other and one another within their own paradigm in Early Modern English, and b) to analyse the use and distribution of these reciprocals to determine the date and the circumstances that contributed to the adoption of each other over one another for the expression of reciprocity in the history of English. The source of evidence comes from the Early English Books Online Corpus (for the period 1473-1700) and the Old Bailey Corpus (for the period 1674-1913)